The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/cancers12123841
|View full text |Cite
|
Sign up to set email alerts
|

Melphalan, Etoposide, and Carboplatin Megatherapy with Autologous Stem Cell Transplantation in Children with Relapsing or Therapy-Resistant Extracranial Germ-Cell Tumors—A Retrospective Analysis

Abstract: Pediatric germ cell tumors (GCTs) are a group of chemosensitive malignancies with a 90% curability rate. We report a series of children with relapsing or therapy-resistant GCT treated with melphalan–etoposide–carboplatin high-dose chemotherapy (HDCT) and autologous stem cell transplantation. This consisted of 18 children, either with GCTs after relapse (nine patients) or with an unsatisfactory response to first-line chemotherapy (nine patients), who underwent HDCT. The HDCT regimens MEC1 (carboplatin 1500 mg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…We used a melphalan/etoposide/carboplatin regimen, which was different from the studies that conducted HDC in OSA. This regimen has already been used for a variety of childhood cancers and is familiar to pediatricians ( 20 22 ). All of these medications are known to be effective in OSA, and we have confirmed through a previously reported pilot study that the melphalan/etoposide/carboplatin regimen showed good treatment results, especially in localized OSA patients with low-degree necrosis ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…We used a melphalan/etoposide/carboplatin regimen, which was different from the studies that conducted HDC in OSA. This regimen has already been used for a variety of childhood cancers and is familiar to pediatricians ( 20 22 ). All of these medications are known to be effective in OSA, and we have confirmed through a previously reported pilot study that the melphalan/etoposide/carboplatin regimen showed good treatment results, especially in localized OSA patients with low-degree necrosis ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…One recent cohort study included 18 children with R/R GCTs in Poland who were treated with melphalan-etoposide-carboplatin HDCT; they showed 5-year OS and 5-year EFS of 76% and 70.8%, respectively. Patients younger than 4 years of age who received HDCT combined with ASCT had an even higher survival rate [ 88 ]. Another recent AIEOP report considered 16 out of 21 children with R/R GCTs who received HDCT; 13 out of 16 (81%) patients were alive without treatment-related death [ 72 ].…”
Section: High Dose Chemotherapy and Autologous Stem Cell Transplantat...mentioning
confidence: 99%
“…The 5-year OS and 5-year EFS was 76% and 70.8%. For the children younger than 4 years old, the OS and EFS were even higher [ 88 ].…”
Section: High Dose Chemotherapy and Autologous Stem Cell Transplantat...mentioning
confidence: 99%